2022
DOI: 10.1371/journal.pone.0264549
|View full text |Cite
|
Sign up to set email alerts
|

Integrating genomic information and productivity and climate-adaptability traits into a regional white spruce breeding program

Abstract: Tree improvement programs often focus on improving productivity-related traits; however, under present climate change scenarios, climate change-related (adaptive) traits should also be incorporated into such programs. Therefore, quantifying the genetic variation and correlations among productivity and adaptability traits, and the importance of genotype by environment interactions, including defense compounds involved in biotic and abiotic resistance, is essential for selecting parents for the production of res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 97 publications
(143 reference statements)
1
5
0
Order By: Relevance
“…In our study, the ssGBLUP models showed a constant increase in additive variance estimates compared to the ABLUP models at all sites, except for the “without inbreeding” scenario at the ILRI site. This is in line with results reported for growth traits in other tree species, for example, Eucalyptus [ 47 , 48 ] , lodgepole pine [ 38 ], white spruce [ 49 ], and loblolly pine [ 50 ]. However, studies on other tree species have reported that models using genomic evaluation (GBLUP or ssGBLUP) show decreased or similar additive variance estimates compared to models using pedigree-based information only for growth and wood quality traits [ 51 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the ssGBLUP models showed a constant increase in additive variance estimates compared to the ABLUP models at all sites, except for the “without inbreeding” scenario at the ILRI site. This is in line with results reported for growth traits in other tree species, for example, Eucalyptus [ 47 , 48 ] , lodgepole pine [ 38 ], white spruce [ 49 ], and loblolly pine [ 50 ]. However, studies on other tree species have reported that models using genomic evaluation (GBLUP or ssGBLUP) show decreased or similar additive variance estimates compared to models using pedigree-based information only for growth and wood quality traits [ 51 53 ].…”
Section: Discussionsupporting
confidence: 90%
“…Wood density (WD) from 5 mm increment cores was measured at approximately breast height. See details on core sampling, transportation and analyses in Cappa et al [ 7 ]. Wood density data represents the relative density on an oven-dry weight basis.…”
Section: Methodsmentioning
confidence: 99%
“…Wood density data represents the relative density on an oven-dry weight basis. Average WD was calculated as the weighted WD of individual tree rings weighted by their ring width, to better represent the density of the whole tree [ 7 ]. Microfibril angle (MFA) was determined by X-ray diffraction on the radial face of the individual growth rings (see Ukrainetz et al [ 73 ] for details).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations